Rhodotorula minuta: uncommon yeast isolated as the causative agent of a right hip joint infection - DURMUŞOĞLU, LÜTFİYE (MASSON EDITEUR, 2005)
Rhodotorula species including Rhodotorula minuta are emerging yeast pathogens defined particularly in immunocompromised patients. In this study the patient was a woman with a history of diabetes mellitus (DM) and uterus cancer, which was treated with chemotherapy following hysterectomy. The patient had more than one operation on her hip joint due to several complaints including restriction in movement and severe pain. The cultures obtained during operations revealed several microorganisms including Candida albicans, Enterobacter cloacae, ESBL (+) Escherichia coli and lastly R. minuta. The last agent, R. minuta was treated successfully with fluconazole. This is the second case of hip joint infection caused by R. minuta, which was hardly isolated following a tong period of cultivation. (c) 2005 Published by Elsevier SAS.
Keywords: Rhodotorula minuta; hip joint infection; FUNGI